2010
DOI: 10.1007/s10823-010-9116-8
|View full text |Cite
|
Sign up to set email alerts
|

Remembering Sacrifices: Attitude and Beliefs Among Second-generation Korean Americans Regarding Family Support

Abstract: Korean immigration peaked in the mid-1980s, so that large cohorts of post-1965 immigrants are now approaching or entering retirement. As the baby boomer generation ages, few studies have examined how the lack of retirement savings and eldercare plans combined with cultural expectations such as filial piety may pose challenges for aging Korean immigrants and their adult children. This exploratory study examines attitudes and beliefs among 1.5 and 2nd generation Korean American adults regarding filial expectatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 28 publications
(19 reference statements)
3
23
1
Order By: Relevance
“…Studies in Asian cultures have found that firstborn sons naturally assume responsibility in decision‐making, as influenced by traditional expectations of filial duty . Stressors common to firstborns from diverse cultures include filial burden, unspoken expectations, sibling conflict, and perceived family judgment …”
Section: Discussionmentioning
confidence: 99%
“…Studies in Asian cultures have found that firstborn sons naturally assume responsibility in decision‐making, as influenced by traditional expectations of filial duty . Stressors common to firstborns from diverse cultures include filial burden, unspoken expectations, sibling conflict, and perceived family judgment …”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in Asian American families who have diabetes patients reported acknowledgment by their family members of the high level of emotional fluctuations experienced by the patient, 35 yet providing physical support is often considered easier than providing emotional support in Asian families. 36 …”
Section: Discussionmentioning
confidence: 99%
“…As compared to Chinese women, their Korean counterpart was given a role that might burden them more in caring for the family, which involved multiple responsibilities pushing them to prioritize supporting the family than their own health (Ahn et al, 1998;Song et al, 2012). Studies regarding gender role strain of Korean women can be observed not only in preventive health behaviors but also in chronic disease managements (Ahn et al, 1998;Yoo and Kim, 2010;Park and Kim, 2012). Korean Chinese could not be encouraged to go for mammogram in spite of existing nation-wide cancer screening program in China (Chan et al, 2007).…”
Section: Discussionmentioning
confidence: 99%